2020
DOI: 10.33271/mining14.02.075
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of tunnel boring machine penetration rate using ant colony optimization, bee colony optimization and the particle swarm optimization, case study: Sabzkooh water conveyance tunnel

Abstract: The purpose of this study is to use a novel approach to estimate the tunnel boring machine (TBM) penetration rate in diverse ground conditions. Methods. The methods used in this study include ant colony optimization (ACO), bee colony optimization (BCO) and the particle swarm optimization (PSO). Moreover, a comprehensive database was created based on machine performance using penetration rate (m/h) as an output parameteras well as intact rock and rock mass parameters including uniaxial compressive strength (UCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…However, Salimi et al [47] mentioned that the boreability of rock decreases with the increase in UCS. Afradi et al [3] used a comprehensive database including uniaxial compressive strength, Brazilian tensile strength, RQD, cohesion, elasticity modulus, Poisson's ratio, density, joint angle and joint spacing as input parameters for estimating penetration rate. Mahdevari et al [41] employed uniaxial compressive strength, tensile strength, brittleness index, distance between the plane of weakness, alpha angle and machine parameters Fig.…”
Section: Tbm Characteristics and Data Identificationmentioning
confidence: 99%
“…However, Salimi et al [47] mentioned that the boreability of rock decreases with the increase in UCS. Afradi et al [3] used a comprehensive database including uniaxial compressive strength, Brazilian tensile strength, RQD, cohesion, elasticity modulus, Poisson's ratio, density, joint angle and joint spacing as input parameters for estimating penetration rate. Mahdevari et al [41] employed uniaxial compressive strength, tensile strength, brittleness index, distance between the plane of weakness, alpha angle and machine parameters Fig.…”
Section: Tbm Characteristics and Data Identificationmentioning
confidence: 99%
“…For future works, it is suggested to use other novel heuristic algorithms such as shark smell optimization and shuffled frog leaping algorithm to predict the penetration rate of the tunnel boring machine. [93] TBM penetration rate (m/h) 0.72 0.18 Queens water tunnel Yagiz and Karahan [14] TBM penetration rate (m/h) 0.66 0.20 Queens water tunnel Afradi et al [91] TBM penetration rate (m/h) 0.97 0.48 Beheshtabad water conveyance tunnel Adoko et al [1] TBM penetration rate (m/h) 0.66 0.22 Queens water tunnel Afradi et al [29] TBM penetration rate (m/h) 0.97 0.34 Sabzkooh water conveyance tunnel…”
Section: Discussionmentioning
confidence: 99%
“…Namli and Bilgin [28] developed a model to predict daily advance rates of EPB-TBMs. Afradi et al [29] suggested a new method for TBM penetration rate using ant colony optimization, bee colony optimization and the particle swarm optimization. The aim of this paper is to show the application of ANN, SVM and GEP for prediction of TBM penetration rate in Chamshir water conveyance tunnel which is considered as one the most important TBM tunneling projects in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The root mean squared error (RMSE) is considered as a measure of absolute error between precipitation and observation. In this study, in order to evaluate the accuracy and performance of the models, the coefficients of determination (R 2 ) and root mean square error (RMSE) is used [36].…”
Section: Evaluation Criteriamentioning
confidence: 99%